PROBLEMATIKA PENGEMBANGAN KARIR TENAGA PENDIDIK DI SMA NEGERI 8 KABUPATEN BATANGHARI - Khaidir, Firman (Jurnal Ilmiah Bina Edukasi, 2020)
This aims of this research are to investigate teachers’ problems related to the career development and to find out the benefits of training for the development of teachers’ career. This research utilized qualitative method. It was conducted at SMA Negeri 8 Batanghari Regency. The research subjects were from 59 teachers. Data collection instruments consisted of observation and interview. All data were analysed descriptively. The results of this study are: Teachers already understand the writing of scientific papers which is a major obstacle in managing promotions. This effort was made in accordance with the needs of teachers in terms of knowing the guidelines for writing scientific papers which so far have not been in line with the supervisors of the Batanghari District Education Office. In addition, the obstacle faced is the motivation of teachers to conduct CAR in each learning process that can be used as scientific writing material so that it can be published in the form of a journal with ISBN / ISSN standards. So that credit numbers are met for teachers to take the promotions.